Effect of reductions in amyloid levels on cognitive change in randomized trials: instrumental variable meta-analysis. (25th February 2021) - Ackley, Sarah F; Zimmerman, Scott C; Brenowitz, Willa D; Tchetgen Tchetgen, Eric J; Gold, Audra L; Manly, Jennifer J; Mayeda, Elizabeth Rose; Filshtein, Teresa J; Power, Melinda C; Elahi, Fanny M; Brickman, Adam M; Glymour, M Maria
Abstract: Objective: To evaluate trials of drugs that target amyloid to determine whether reductions in amyloid levels are likely to improve cognition. Design: Instrumental variable meta-analysis. Setting: 14 randomized controlled trials of drugs for the prevention or treatment of Alzheimer's disease that targeted an amyloid mechanism, identified from ClinicalTrials.gov. Population: Adults enrolled in randomized controlled trials of amyloid targeting drugs. Inclusion criteria for trials vary, but typically include adults aged 50 years or older with a diagnosis of mild cognitive impairment or Alzheimer's disease, and amyloid positivity at baseline. Main outcome measures: Analyses included trials for which information could be obtained on both change in brain amyloid levels measured with amyloid positron emission tomography and change in at least one cognitive test score reported for each randomization arm. Results: Pooled results from the 14 randomized controlled trials were more precise than estimates from any single trial. The pooled estimate for the effect of reducing amyloid levels by 0.1 standardized uptake value ratio units was an improvement in the mini-mental state examination score of 0.03 (95% confidence interval −0.06 to 0.1) points. This study provides a web application that allows for the re-estimation of the results when new data become available and illustrates the magnitude of the new evidence that would be necessary to achieve a pooled estimate supporting the benefit of reducing amyloid levels. Conclusions: Pooled evidence from available trials reporting both reduction in amyloid levels and change in cognition suggests that amyloid reduction strategies do not substantially improve cognition.